2004
DOI: 10.4269/ajtmh.2004.70.651
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Diarrhea Through the Use of Household-Based Ceramic Water Filters: A Randomized, Controlled Trial in Rural Bolivia

Abstract: Ceramic water filters have been identified as one of the most promising and accessible technologies for treating water at the household level. In a six-month trial, water filters were distributed randomly to half of the 50 participating households in a rural community in Bolivia; the remaining households continued to use customary water handling practices and served as controls. In four rounds of sampling following distribution of the filters, 100% of the 96 water samples from the filter households were free o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 25 publications
3
82
1
2
Order By: Relevance
“…One promising technology is porous ceramic filtration. Studies of relatively expensive, commercially produced ceramic filtration devices have suggested that these filters can provide an effective barrier against microbial pathogen indicators in water and that interventions are associated with significant health gains in users versus non-users of the technologies (Clasen et al 2004(Clasen et al , 2005(Clasen et al , 2006. Successful field trials of more expensive filters have suggested that low-cost, locally produced filters may also be promising technologies for increasing access to safe water at the household level.…”
Section: Systematic Reviews Of Field Trials Have Suggested Thatmentioning
confidence: 99%
“…One promising technology is porous ceramic filtration. Studies of relatively expensive, commercially produced ceramic filtration devices have suggested that these filters can provide an effective barrier against microbial pathogen indicators in water and that interventions are associated with significant health gains in users versus non-users of the technologies (Clasen et al 2004(Clasen et al , 2005(Clasen et al , 2006. Successful field trials of more expensive filters have suggested that low-cost, locally produced filters may also be promising technologies for increasing access to safe water at the household level.…”
Section: Systematic Reviews Of Field Trials Have Suggested Thatmentioning
confidence: 99%
“…In recent years, pointof-use systems have gained new-found popularity as solutions to water issues in the developing world [2]. Safe storage is an important aspect of some systems used for drinking water treatment or safe storage containers may be used as a stand-alone technology for protecting water quality where the main source of contamination is improper handling [3]. Ideally, POU systems can also safeguard against stored water contamination in the home through unsafe water handling practices, known to be a major cause of degraded drinking water quality [4].…”
Section: Introductionmentioning
confidence: 99%
“…Low cost clay filtration for drinking water treatment in developing countries is diverse, varying by overall design, production method, clay and other materials, quality assurance and quality control, procedures, burnout material, firing temperatures and methods, and sometimes chemical (e.g., colloidal silver) amendments, and other characteristics [10]. Unlike chemical or thermal disinfection, clay filters do not significantly change water taste or temperature and do reduce turbidity [3,11]. Filters have functional stability in the sense that they have only one moving part (the tap) and require no external energy source [12].…”
Section: Introductionmentioning
confidence: 99%
“…5 Point-of-use disinfection of drinkingwater with chlorine and filtration, and recently with a new flocculant-disinfectant, has been proven to reduce the incidence of diarrhoea in children in several studies in developing countries. [6][7][8][9][10] Although chlorine is readily available and highly successful in treating unsafe drinkingwater, it has not been widely adopted by at-risk households without substantial efforts being made by local field staff to change behaviour. One reason may be that adding chlorine to drinking-water often adversely affects its taste and odour and does not make the water appear cleaner.…”
Section: Introductionmentioning
confidence: 99%